2012
DOI: 10.1111/j.1399-5448.2012.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced physical fitness in children and adolescents with type 1 diabetes

Abstract: SUMMARYAims: To evaluate motor performance and cardiorespiratory function in youths with type 1 diabetes in comparison with age-matched control group; and to analyse the influence of physical activity level, anthropometric and physical fitness parameters on long-term metabolic control. Methods: 106 youths with diabetes and 130 healthy youths aged 8-18 were assessed by the Eurofit Test Battery regarding motor performances, cardiorespiratory fitness (VO 2max ), skinfold thickness, and body mass index. Physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
59
3
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 18 publications
7
59
3
12
Order By: Relevance
“…Children and adolescents with T1DM have low PA levels (10)(11)(12). Thus, they are at high risk for psychosocial morbidities including depression, heightened anxiety, low health-related quality of life (HRQoL), low self-efficacy, low adherence to treatment, and low metabolic control (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents with T1DM have low PA levels (10)(11)(12). Thus, they are at high risk for psychosocial morbidities including depression, heightened anxiety, low health-related quality of life (HRQoL), low self-efficacy, low adherence to treatment, and low metabolic control (13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Among prepubertal boys with T1DM the participation in physical activity does not decrease compared to their healthy counterparts, while lower activity may be noted among girls [27]. However, in adolescence a decrease in physical activity may be noted both in girls and in boys with diabetes compared to their healthy peers [27,28].…”
Section: Discussionmentioning
confidence: 89%
“…U chłopców z T1DM przed okresem pokwitania udział w AF nie zmniejsza się w stosunku do zdrowych rówieśników, natomiast u dziewcząt mogą występować spadki [27]. Ale już w wieku młodzieńczym odnotowuje się spadek AF zarówno u dziewcząt jak i chłopców w stosunku do ich zdrowych rówieśników [27,28]. Różnice pogłębiają się, gdy kontrola poziomu glikemii jest dokonywana z mniejszą częstotliwością [29,30].…”
Section: Discussionunclassified
“…It is suggested that children with diabetes, because of the fear of hypoglycemia as a consequence of exercise, participate less intensively [14]. In sport activities, have less daily physical activity, and may have less skill to perform such tests than non-diabetic peers [15]. Further possibilities are that early complications of diabetes as diabetic myopathy may contribute to reduced physical fitness achievements.…”
Section: Comparison Of the Body Composition Valuesmentioning
confidence: 99%